Feasibility of Healthy and Fresh Smoothies: Opportunities and Challenges from the Consumer Perspective in Central Cikarang - Sari, Nadilah Sintia; Permana, Muhammad Rizki; Mauizhoh, Nida Wahdah; Sagita, Lisna; Muslihat, Rivaldi (Review: Journal of Multidisciplinary in Social Sciences, 2025)
This study examines the opportunities and challenges of the "Smoothies Healthy and Fresh" business at the Central Cikarang Clean Market from a consumer perspective. This feasibility study uses a qualitative approach to analyze marketing, operational, human resource, and financial aspects. The results show that healthy lifestyle trends and digital market dynamics create significant opportunities for the natural-ingredient smoothie business. Digital-based marketing strategies and direct promotions support business growth with a broad target market, ranging from children to adults. Operationally, this business emphasizes cleanliness, quality ingredients, and professional customer service. From a financial perspective, projections show promising net profits with the potential for a quick return on investment. However, competitive challenges in the healthy beverage industry can be overcome through product innovation, flavor development, and adaptation to consumer feedback. This study concludes that "Smoothies Healthy and Fresh" has the potential to grow with a holistic, adaptive, and consumer-oriented strategy.